Interpreting engineering drawings - Branoff, Theodore J. (Cengage Learning, 2016)
This book offers comprehensive, state-of-the-art training that shows readers how to create professional-quality engineering drawings that can be interpreted with precision in today's technology-based industries. This flexible textbook offers unsurpassed coverage of the theory and practical applications that you'll need as readers communicate technical concepts in an international marketplace. All material is developed around the latest ASME drawing standards, helping readers keep pace with the dynamic changes in the field of engineering graphic.